Analysis of Pros and Cons of New Province Expansion in Papua - Afisa, Afisa; Habibullah, Akhmad; Khairiyah, Miftahul; Widodo, Agus Setio (Humanus, 2024)
This study aims to examine the analysis of mass media coverage sentiment about the division of a new province in Papua. Using qualitative analysis with Q-DAS software, namely Nvivo 12Plus, this research collects data from online news and previous research related to the expansion of the Papua Province. The results show that there are pro and contra sentiments, where activists and citizens are more critical of it and reject it, while the government is more supportive of it. This analysis also uncovers various narratives in the media that highlight the potential benefits of regional expansion, such as development, better public services, and preserving local culture. However, there are also concerns about financial and economic inefficiencies and a lack of representation of indigenous people's voices. Relations between the different actors are complex, with decentralization principles governing interactions between the central government and the newly created local governments. This research emphasizes the need for a thorough evaluation, considering social, economic, political, and cultural impacts, and involving all relevant stakeholders in the decision-making process.